Multiple Bony Injuries on Bone Scan in a Case of Unsuspected Child Abuse - Ya-Wen Chuang; Chien-Chin Hsu; Chin-Chuan Chang; Chia-Yang Lin; Hsiu-Lan Chu; Ying-Fong Huang; Yu-Chang Tyan (Case Reports in Medicine)
This case is described of an eleven-month-old infant with lower limbs swelling and the left elbow skeletal malformation following a fall. The radionuclide bone scan was performed to exclude bone infection or congenital skeletal anomaly. The images unexpectedly showed multiple increased radioactive foci throughout the whole body. It was a strong probability of child abuse. All lesions are readily apparent on the following plain film radiographs and MRI.